If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + 2c = 1 Reorder the terms: 2c + 2d = 1 Solving 2c + 2d = 1 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2d' to each side of the equation. 2c + 2d + -2d = 1 + -2d Combine like terms: 2d + -2d = 0 2c + 0 = 1 + -2d 2c = 1 + -2d Divide each side by '2'. c = 0.5 + -1d Simplifying c = 0.5 + -1d
| 0.25(115-x)=35.65 | | 3x^0+9=78 | | h^2-17h+60=0 | | 4-v5=0 | | 18(2)+7(-2)= | | -3c+d=15 | | 8-1/3x=1/9x | | 15(-0.2-2x)+4.8=7.4-5.5(5.4x+1) | | 4/5n=16 | | 27x^6-48x^4=0 | | 9(2)-4(-2)= | | 4(3+x)=4(4x-1)-80 | | x+20=25 | | 4m+5n-3(9m-9n)= | | 6+5i/(-2i)=0 | | 2c+3d=1 | | 3x^10+9=78 | | 4/5(a+5)=a | | -6x^5y^5+30x^4y^4-12x^3y^3=0 | | 1/4+11/8 | | 3x^2+9=78 | | 4m+12=8m-4 | | -x+5=-x-4 | | -3-(2-6p)= | | a/4-1=a/3+4 | | 3x+10=65 | | a=7-1 | | 6a-4/8+2-7a/3=4-5a/2 | | -6x^5y^4+15x^3y^3-9x^2y^2=0 | | -52+22= | | 48x+24x=384+9x | | 6=6-8x-3x |